2018
DOI: 10.1038/s41467-018-02975-w
|View full text |Cite
|
Sign up to set email alerts
|

Development of a chimeric Zika vaccine using a licensed live-attenuated flavivirus vaccine as backbone

Abstract: The global spread of Zika virus (ZIKV) and its unexpected association with congenital defects necessitates the rapid development of a safe and effective vaccine. Here we report the development and characterization of a recombinant chimeric ZIKV vaccine candidate (termed ChinZIKV) that expresses the prM-E proteins of ZIKV using the licensed Japanese encephalitis live-attenuated vaccine SA14-14-2 as the genetic backbone. ChinZIKV retains its replication activity and genetic stability in vitro, while exhibiting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
70
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 70 publications
(86 reference statements)
0
70
0
Order By: Relevance
“…The 10.8 kb genome of ZIKV encodes a single polyprotein that, upon action of host and viral proteases, forms three structural proteins (C, PrM, and E) and seven nonstructural proteins (NS1-5 NS2A, NS2B, NS3, NS4A, NS4B, and NS5) (Ye et al, 2016). Numerous approaches are being employed to develop live attenuated virus (Shan et al, 2017), inactivated whole virus (Sumathy et al, 2017), subunit DNA/RNA vaccines (Pardi et al, 2017;To et al, 2018), virus like particles (Espinosa et al, 2018;Salvo et al, 2018), over virus vectored (Xu et al, 2018), and chimeric ZIKV (Kum et al, 2018;Li et al, 2018) vaccines pertaining to several benefits including economical and long-term immunity. But only a few of them have generated appropriate prophylactic responses in tested in vivo models.…”
Section: Chimeric Zika Virusmentioning
confidence: 99%
“…The 10.8 kb genome of ZIKV encodes a single polyprotein that, upon action of host and viral proteases, forms three structural proteins (C, PrM, and E) and seven nonstructural proteins (NS1-5 NS2A, NS2B, NS3, NS4A, NS4B, and NS5) (Ye et al, 2016). Numerous approaches are being employed to develop live attenuated virus (Shan et al, 2017), inactivated whole virus (Sumathy et al, 2017), subunit DNA/RNA vaccines (Pardi et al, 2017;To et al, 2018), virus like particles (Espinosa et al, 2018;Salvo et al, 2018), over virus vectored (Xu et al, 2018), and chimeric ZIKV (Kum et al, 2018;Li et al, 2018) vaccines pertaining to several benefits including economical and long-term immunity. But only a few of them have generated appropriate prophylactic responses in tested in vivo models.…”
Section: Chimeric Zika Virusmentioning
confidence: 99%
“…Studies from a number of groups have reported the protective efficacy of inactivated virus vaccines, DNA vaccines, viral vector-based vaccines and mRNA vaccines 5456,68,7076 (Table 1). DNA vaccines expressing variations of the prM-ENV antigen were quickly developed and tested successfully for efficacy in both mice and monkeys 70 .…”
Section: Protection In Pre-clinical Modelsmentioning
confidence: 99%
“…mRNA vaccines expressing wild-type or modified prM-ENV antigens, leading to the generation of sub-viral particles were able to protect mice with a single dose as low as 10 µg 54 or 50 µg for monkeys 55 . Several live-attenuated vaccines have also been developed, based on the Yellow Fever Virus (YFV) YF17D model, the JEV vaccine SA14–14-2 backbone, or attenuated through systematic deletions in the 3′UTR region in the ZIKV genome 7476 . All live-attenuated ZIKV vaccines have proved immunogenic and protective in mice and monkeys.…”
Section: Protection In Pre-clinical Modelsmentioning
confidence: 99%
See 2 more Smart Citations